The Dual Role of Women in Improving Family Welfare Case Study in Gegerung Village Lingsar District - Safitri, Karisma; Apriawan, Andika; Ningsih, Dewi Puspita; Suryadmaja, Galih (International Journal of Social Sciences and Humanities, 2023)
This study aims to: 1) Find out how women's roles improve family welfare in Gegerung Village. 2) Find out the impact of women's dual roles on the economy and women's dual roles on children's education in Gegerung Village. This study is a qualitative study that uses descriptive data in the form of written or spoken language from people and actors observed. The data sources for this study consisted of working women, husbands, and children in Gegerung Village. The number of respondents consisted of 26 people. The study was conducted in Gegerung Village, Lingsar District, West Lombok Regency. The object of this study is the dual role of women in improving family welfare in Gegerung Village. Data collection was carried out using interview, documentation, and observation methods. Furthermore, the data obtained were analyzed by data reduction, data presentation, and drawing conclusions. The results of the study indicate that the dual role of women in improving family welfare in Gegerung Village has a dual role in improving family welfare by becoming wives, mothers, and workers. They can contribute to family welfare in various ways such as working in the office, managing the household, and various other businesses. Women as housewives and workers carry out dual activities, seeking additional income, and playing a role in seeking sustenance. The establishment of mutual understanding between family members as a positive impact of women's dual roles, despite the negative impacts such as limited time for the family.